Larangan Penggunaan Telepon Saat Mengemudi - Panggabean, Lisa Alawiyah (Jurnal El-Thawalib, 2022)
Highway safety is a state of mind. An accident is not a lack of thought but a loss of concentration while driving. Concentrating is very important in driving to get a safe ride. Traffic is a process that occurs on the highway. One of the problems regarding the use of mobile phone communication devices (hand phones) by motorcyclists when driving. The use of mobile phone communication devices while driving is very dangerous if these activities are not stopped immediately. This activity also harms other road users, maybe the driver who uses a mobile phone is not disturbed but for other road users it is very disturbing. From these problems, the writer wants to know how the role of the traffic police in the implementation of Law No. 22 of 2009 Article 106 Paragraph (1) regarding the prohibition of using mobile phones while driving a motorized vehicle is in the city of Padangsidimpuan, as well as how the fiqh siyasah review of the role of the traffic police in Implementation of Law No. 22 of 2009 concerning the Prohibition of Using Mobile Phones While Driving a Motorized Vehicle in Padangsidimpuan City. The result of this research is that the role of the traffic police in the implementation of Law no. 22 of 2009 article 106 paragraph (1) concerning the prohibition of using mobile phones while driving in Padangsidimpuan City in general has played a good role, especially in violations of article 106. However, it is necessary to increase the enforcement of traffic violations in providing sanctions that deter perpetrators from committing violations. . As for the fiqh siyasa review of the role of the traffic police in implementing the law, the importance of the role of a leader is to oblige the public to obey and obey the rules that have been set.